Lectotypification of Quercus brandisiana Kurz and the significance of the leaf epidermal features to its taxonomy - Li, Qiansheng; Deng, Min; Li, Quanjian; Coombes, Allen (Phytotaxa, 2014)
Based on a survey of literature and specimens, the lectotype of Quercus brandisiana Kurz is designated here. Information on its distribution, taxonomy and leaf epidermal features is given. Features that distinguish Q. brandisiana from closely related species are given and a key to their identification is provided.